Essential Skills for Health Communication, Barriers, Facilitators and the Need for Training: Perceptions of Healthcare Professionals from Seven European Countries - Zota, Dina; Diamantis, Dimitrios V; Katsas, Konstantinos; Karnaki, Pania; Tsiampalis, Thomas; Sakowski, Piotr; Christophi, Costas A.; Ioannidou, Eleni; Darias-Curvo, Sara; Batury, Victoria Luise; Berth, Hendrik; Zscheppang, Anja; et al. (My University, 2023)
Many healthcare professionals are unaware of the necessary skills and barriers hindering interpersonal health communication. This study aimed to evaluate the healthcare professional's perception regarding health communication training's necessity, barriers, facilitators and critical skills in health communication. Data from a cross-sectional online survey in the framework of the H-Com project were utilized. The study included 691 healthcare professionals (physicians, nurses, students and allied health professionals) from seven European countries. Only 57% of participants had participated in health communication training, while 88.1% of them indicated a willingness to be trained in health communication. Nurses were more likely (OR = 1.84; 95% CI 1.16, 2.91) to have received such training, compared to physicians. Most examined communication skills, barriers and facilitators of effective communication, and perceived outcomes of successful communication were considered crucial for most participants, although physicians overall seemed to be less concerned. Most agreed perceived outcomes were improved professional-patient relations, patient and professional satisfaction, physical and psychological health amelioration and patients' trust. Nurses evaluated the importance of these communication skills and communication barriers, facilitators and outcomes higher than physicians. Physicians may underestimate the importance of communication skills more than nurses. Health communication should become an integral part of training for all health professionals.
Keywords: communication skills; health communication; health communication training; healthcare professionals